Exposure to 17β-Oestradiol Induces Oxidative Stress in the Non-Oestrogen Receptor Invertebrate Species Eisenia fetida - Heger, Zbynek; Michalek, Petr; Guran, Roman; Havelkova, Barbora; Kominkova, Marketa; Cernei, Natalia; Richtera, Lukas; Beklova, Miroslava; Adam, Vojtech; Kizek, Rene (PloS one, 2015)
BACKGROUND: The environmental impacts of various substances on all levels of organisms are under investigation. Among these substances, endocrine-disrupting compounds (EDCs) present a threat, although the environmental significance of these compounds remains largely unknown. To shed some light on this field, we assessed the effects of 17β-oestradiol on the growth, reproduction and formation of free radicals in Eisenia fetida. METHODOLOGY/PRINCIPAL FINDINGS: Although the observed effects on growth and survival were relatively weak, a strong impact on reproduction was observed (50.70% inhibition in 100 μg/kg of E2). We further demonstrated that the exposure of the earthworm Eisenia fetida to a contaminant of emerging concern, 17β-oestradiol (E2), significantly affected the molecules involved in antioxidant defence. Exposure to E2 results in the production of reactive oxygen species (ROS) and the stimulation of antioxidant systems (metallothionein and reduced oxidized glutathione ratio) but not phytochelatins at both the mRNA and translated protein levels. Matrix-assisted laser desorption/ionization (MALDI)-imaging revealed the subcuticular bioaccumulation of oestradiol-3,4-quinone, altering the levels of local antioxidants in a time-dependent manner. CONCLUSIONS/SIGNIFICANCE: The present study illustrates that although most invertebrates do not possess oestrogen receptors, these organisms can be affected by oestrogen hormones, likely reflecting free diffusion into the cellular microenvironment with subsequent degradation to molecules that undergo redox cycling, producing ROS, thereby increasing environmental contamination that also perilously affects keystone animals, forming lower trophic levels.
Keywords: Animals; rozmnožování; Antioxidants; oxidační stres; Soil Pollutants; Oligochaeta; Reproduction; Oxidative Stress; látky znečišťující půdu; Reactive Oxygen Species; peroxidace lipidů; regulace genové exprese; Lipid Peroxidation; antioxidancia; reaktivní formy kyslíku; Gene Expression Regulation; zvířata; Estradiol; estradiol